CYTOKINE AND LEUKOTRINE (LTB4) STIMULATION PROPERTIES OF PONGAMIA PINNATA BARK AQUEOUS EXTRACTS - MANIKANNAN MATHAIYAN; DINESH SUBRAMANIYAM (International Journal of Pharma and Bio Sciences, 2015)
Immunotherapy is a novel approach to combat cytokine mediated diseases. Immunomodulatory drugs are known to play a vital role in altering the cytokine profile and the outcome of disese. Several medicinal plants were shown to possess immune modulatory properties. One of the popular Indian medicinal plant known as Pongamia pinnata (P. pinnata) has been extensively studied for its bioactive properties. We have reported in our previous study for P. pinnata’s immune modulatory properties however this study extended to investigate further its immunomodulatory property of bark extracts. In this study it was found that bark extracts of P. pinnata profoundly increased the human IFN- γ and IL-10 which also support our previous findings with seeds extracts. These findings strongly suggest that P. pinnata’s immunomodulatory role on human immune cells.